HOW MUCH WEAR PRECAUTIONARY PRINCIPLE - PHILIPPE PIRNAY (Romanian Society of Oral Rehabilitation, 2015)
Although topical issues, GMOs nanotechnology, nuclear shale gas to demonstrate the paradox of our age: it is that of increasing knowledge, it is also that of the rise of collective fears, often irrational [1]. For Bernard Accoyer, the legitimate requirement of an ever greater security, the dream of a risk-free society, the utopia of immortality divert the progress of its goal of improving the living conditions of each of us. However, the advantages are that humanity has recently learned of science are unprecedented in the history of mankind. Open prospects offer hope of a better life who have contributed notably to the reduction of illness, suffering, death. This is the case of the medical and dental science.